Revisiting the Theory of Broken Windows Policing - Piston, Spencer (International Journal of Criminology and Sociology, 2023)
How has the academy contributed to the horrors of policing in the United States? While many scholars study policing, few do so from a self-reflective position, which would examine how the production of knowledge has often legitimized policing’s harms. As part of a larger effort to encourage researchers to come to terms with the role we have played in facilitating contemporary atrocities, here I reconsider political scientist James Q. Wilson and criminologist George L. Kelling’s 1982 “Broken Windows” essay, as well as its intellectual legacy. Their essay is best known for speculating that police foot-patrols, by cracking down on low-level offenses, will reduce serious crime. While this speculation has become the subject of much public and academic debate, the relationship between policing and crime is only a secondary point in the article. Unfortunately, focusing on this secondary point has led scholarly and public discourse to distort the essay’s arguments. I correct this distortion through a close reading of the essay. Wilson and Kelling argue that the primary objective of the police should be to maintain order rather than to prevent crime or even to enforce the law. As such, police should discourage behavior inconsistent with neighborhood standards (even if it is not criminal) and should also remove “disorderly” people from public life (even if they are not breaking the law). Indeed, Wilson and Kelling actually endorse illegal actions in certain instances: when these actions are committed by either police or vigilantes to fashion and maintain the authoritarian, classist, ableist, and racist order that the authors envision. After discussing how an accurate understanding of the original “Broken Windows” article has the potential to reorient contemporary studies policing, I conclude by locating broken windows theory as an important member of a family of harmful ideas, generated by academics, that have underwritten a wide range of authoritarian policing practices.